Nigeria-China Bilateral Relations: Trade, Investment and Political Influence - Idrees, Mahmud Gana; Bashir, Adamu Abdullahi; Zurkallaini, Alhaji Maikano; Abubakar, Suleiman Dauda; Fauziyya, Mohammed Rabiu (Kashere Journal of Politics and International Relations, 2024)
Nigeria-China bilateral relations have changed dramatically since diplomatic ties were established in 1971, covering commerce, investment, and political partnership. This qualitative research dives into the historical setting, looking at how the relationship progressed from initial reluctance to vigorous economic participation. China has made significant investments in Nigeria, notably in infrastructure projects, although there are still concerns about trade imbalances and possible economic reliance. Diplomatically, both countries have increased ties, with Nigeria backing China's international ambitions, particularly its pursuit for a permanent seat on the United Nations Security Council. The political economy approach provides a theoretical framework for evaluating the relationship's multidimensional dynamics, focusing on the interaction of economic interests, political power, and societal repercussions. Diversifying Nigeria's trade partners, improving local firms, and maintaining openness in investment agreements are among the recommendations made to promote mutual benefit and long-term sustainability.